Correlation of umbilical blood pH and outcome in meconium stained deliveries - Misra, Saheli; Sarkar, Sourav; Das, Niloy Kumar (Asian Journal of Medical Sciences, 2016)
Background: Umbilical cord blood analysis is assumed to give a picture of acid base balance of the infant at the moment of birth when umbilical circulation is arrested by clamping of the cord. Meconium stained deliveries often cause anxiety in the minds of clinicians attending such newborn. Aims and Objectives: To study the correlation of umbilical cord pH with apgar and outcome and predict a model to help us to detect cases of meconium that need active monitoring and intervention. Materials and Methods: This was a prospective observational study.86 newborn born to mothers with meconium at artificial rupture of membranes was enrolled for the study All newborn had arterial blood gas analysis from umbilical cord. Results: The pH of umbilical blood showed positive correlation with apgar scores at 1minute (r=0.46) and negative correlation with thick meconium(r=-0.35) and outcome (r=0.36). Conclusion: The correlation though not strong are suggestive of the fact that meconium deliveries with poor apgar and thick meconium should be monitored before discharge. Asian Journal of Medical Sciences Vol.7(4) 2016 113-115